Ultrasound and arterial wall disease - Hennerici, Michael G.; Bäzner, Hansjörg; Daffertshofer, Michael (Cerebrovascular diseases, 2004)
Rapid progress in non-invasive ultrasound techniques has resulted in a wide variety of clinical applications for the assessment of cerebrovascular diseases. Recent highlights in ultrasound research include the evaluation of vascular ageing as a degenerative process, the demonstration of plaque development, motion and vulnerability in atherosclerosis and multi-dimensional as well as innovative imaging techniques (e.g., compound imaging) to depict early and small vascular lesions. In addition, echo-contrast agents have been used to compensate for difficulties in visualising late, severe or subtotal obstructive plaques, but failed to be really superior to conventional techniques as evidenced in a prospective, multi-centre trial (Contrast Enhanced Duplex sonography versus Arteriography Studies - CEDAS). With increasing sophistication of ultrasound methodology, it becomes essential to establish standards for data acquisition and interpretation: three consensus meetings have provided detailed recommendations on quantification of carotid atherosclerosis, characterisation of carotid artery plaques and detection of microembolism by transcranial Doppler as a potential indicator of stroke risk.